Pemanfaatan Limbah Pertanian dalam Menurunkan Dosis Pupuk Anorganik, Meningkatkan Populasi Azospirillum sp. , Nitrogen tanah, Serapan Nitrogen, dan Hasil Jagung pada Inceptisols Jatinangor - Mieke Rochimi Setiawati; Diyah Sri Utami; Reginawanti Hindersah; Diyan Herdiyantoro; Pujawati Suryatmana (Fakultas Pertanian Universitas Padjadjaran, 2021)
Balanced fertilizer is a solution to increase Inceptisols fertility and maize productivity. The aim of this study was to determine the effects and interactions between various fertilizers organic fom agriculture waste with inorganic fertilizers to increase the total population of Azospirillum sp., nitrogen uptake, soil nitrogen and the yield of maize (Zea mays) in Inceptisols Jatinangor. The research was conducted from July 2020 to January 2021 in the experimental screen house at Ciparanje, Agriculture Faculty, Universitas Padjadjaran, Jatinangor, Sumedang, West Java, 724 meters above the sea level. This research design used a randomized block design (RBD) factorial with 16 treatments and three replicates. The first factor was the type of organic fertilizer (O) of four levels: without organic fertilizer (control), 10 tons ha1 of rice straw compost, sugarcane bagasse compost, and oil palm empty fruit bunche compost. The second factor was the dosage of inorganic fertilizers (A) of four levels: without inorganic fertilizer (control), 50%, 75% and 100% dose recommendation inorganic fertilizer. The results showed that no interaction between organic fertilizers and inorganic fertilizers against all the parameters. The independent effect of organic fertilizers had a significant effect on the parameters of the total population of Azospirillum sp., nitrogen uptake and maize yields. The independent effect of inorganic fertilizers has a significant effect on nitrogen uptake and maize yields. Treatment of 10 ton ha-1 of oil palm empty bunche compost and inorganic fertilizer (50% recommendation dose) was the best treatment for dry shelled weight per maize plant on Inceptisols, equal to 88.52 g and 87.96 g each plants.